Groups, Orders, and Laws - Navas-Flores, A (European Mathematical Society Publishing House, 2014)
It is unknown - yet very likely false - whether left-orderable groups satisfying a non-trivial identity must be virtually solvable. Starting from this, we explore several notions/ conjectures/questions that are closely related. As a concrete result, we provide examples of left-orders on the free group satisfying no nontrivial law. © 2014 EMS Publishing House. All rights reserved.